(untitled) (Journal of Hama University, 2025)
The research was carried out during 2023growing season at Agricultural Research Center of AlGhab, GCSAR, Syrian, in order to study the effect of foliar application of boron and potassium on productivity and some quality traits of sugar beet (Beta vulgaris L.) under drought stress during active vegetative growth phase compare to an irrigated control. The experiment designed according to the split plot design with three replicates, the main plots were allocated to drought stress and irrigated control treatments, while subplot were occupied with foliar spraying treatments (control, B, K and BK). Plants were sprayed three times at 40,60,90 days from sowing. The study included in addition to studying theoretical and extractable sugar yield per hectare many qualitative traits (theoretical sugar yield per hectare, extractable sugar yield per hectare, purity %, dough polarity %, juice polarity %, total soluble solids (Brix%). The results of statistical analysis showed that the foliar spraying of BK under both drought and full irrigation conditions was superior to all other treatments in (theoretical and extractable sugar yield, dough polarity, juice purity, and dry matter content in the juice), The obtained results also showed that the spraying of K surpassed spraying of B in most studied characteristics, while the spraying of K, B, BK was superior to control. The study concluded by highlighting the importance of foliar application of boron and potassium in reducing the negative effects of drought stress on the productivity and quality traits of sugar beet.